2014 International Conference on Intelligent Networking and Collaborative Systems 2014
DOI: 10.1109/incos.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DTN Routing Protocols in Realistic Scenario

Abstract: Delay-, disruption-, and disconnection-tolerant networks (DTNs) implement the store-carry-forward (SCF) paradigm for message delivery, which can be used for data transmission when an end-to-end connection may never be reached. A number of SCF routing schemes have been developed to increase performance in various scenarios. In this paper, using the ONE Simulator, we investigate four SCF-based DTN routing protocols-Epidemic, MaxProp, ProphetV2, and Direct Oracle-by varying the number of created messages (message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…One other sophisticated scheme is MaxProp [13], in which the path cost is computed based on the meeting probability of each hop along the destination, and the shortest cost path is selected. Note that our previous work [4] showed that PRoPHETv2 (PV2) [12] outperformed MaxProp in the island scenario. As another example, You et al proposed a hop-count-based heuristic routing protocol for mobile DTNs, which calculates heuristic estimations based on hop count information [14].…”
Section: Forwardingmentioning
confidence: 86%
See 1 more Smart Citation
“…One other sophisticated scheme is MaxProp [13], in which the path cost is computed based on the meeting probability of each hop along the destination, and the shortest cost path is selected. Note that our previous work [4] showed that PRoPHETv2 (PV2) [12] outperformed MaxProp in the island scenario. As another example, You et al proposed a hop-count-based heuristic routing protocol for mobile DTNs, which calculates heuristic estimations based on hop count information [14].…”
Section: Forwardingmentioning
confidence: 86%
“…are stationary and located at some areas that are different from the source node's areas. In our previous study, we compared several popular DTN routing protocols via simulation and found that there is no single best routing algorithm for the island scenario under different conditions (e.g., congestion levels) [4]. This motivated us to develop a new routing protocol that includes efficient buffer management (involving message scheduling) to increase the performance of DTNs in the island scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The performances of DTN, and consecutively VDTN, can be measured by several Key Performance Indicators (KPIs). In this study, we utilize three commonly used KPIs in previous studies on this topic [5,6,7,8,9]. We discuss on each of them in the following subsections.…”
Section: The Key Performance Indicators (Kpis)mentioning
confidence: 99%
“…The Opportunistic Networking Environment (ONE) simulator [32] was used to evaluate the VDTN-based data collections' networking performances. As we mentioned previously, we apply three KPIs for the performance evaluation, namely Delivery Probability, Average Latency, and Overhead Ratio [5,6,7,8,9].…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation